2008
DOI: 10.5194/angeo-26-3341-2008
|View full text |Cite
|
Sign up to set email alerts
|

Periodic traveling compression regions during quiet geomagnetic conditions and their association with ground Pi2

Abstract: Abstract. Recently, Keiling et al. (2006) showed that periodic (∼90 s) traveling compression regions (TCRs) during a substorm had properties of Pi2 pulsations, prompting them to call this type of periodic TCRs "lobe Pi2". It was further shown that time-delayed ground Pi2 had the same period as the lobe Pi2 located at 16 R E , and it was concluded that both were remotely driven by periodic, pulsed reconnection in the magnetotail. In the study reported here, we give further evidence for this association by repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…That is, the in-situ magnetic signature of the Pi2 was observed ∼30 s prior to that visually identified in the magnetometer time-series on the ground. Further, Keiling et al (2008) demonstrated that there was, at times, a magnetic perturbation signature with an amplitude of ∼0.5 nT observed by Geotail at 8-9 R E . Taken together, these results were used to propose that a common source for ground-based and insitu Pi2s, specifically transient reconnection, which could account for both the short time delay between the signals as well as the similar frequency content of the Pi2 waveforms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…That is, the in-situ magnetic signature of the Pi2 was observed ∼30 s prior to that visually identified in the magnetometer time-series on the ground. Further, Keiling et al (2008) demonstrated that there was, at times, a magnetic perturbation signature with an amplitude of ∼0.5 nT observed by Geotail at 8-9 R E . Taken together, these results were used to propose that a common source for ground-based and insitu Pi2s, specifically transient reconnection, which could account for both the short time delay between the signals as well as the similar frequency content of the Pi2 waveforms.…”
Section: Discussionmentioning
confidence: 99%
“…In their studies, Keiling et al (2006Keiling et al ( , 2008 found that there was a small time delay observed between the magnetic signature observed at Cluster situated in the nightside magnetosphere (16-18 R E ) and mid-auroral latitude magnetometers (L = 4.5-6.1). That is, the in-situ magnetic signature of the Pi2 was observed ∼30 s prior to that visually identified in the magnetometer time-series on the ground.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations